Description of Crassolabium unicum sp. n. (Nematoda: Dorylaimida: Qudsianematidae) from Vietnam - Nguyen, Thi Anh Duong; Peña-Santiago, Reyes (Zootaxa, 2021)
Crassolabium unicum sp. n., collected from a natural habitat in Vietnam, is described and illustrated. The new species is characterized by its 0.77–0.94 mm long body, three-layered cuticle, lip region offset by depression and 12–13.5 µm broad, odontostyle 13.5–15 µm long with wide aperture occupying 36–46% of its length, neck 235–260 µm long, pharyngeal expansion 117–131 µm long or occupying 47–52% of total neck length, anterior part of intestine presenting very distinct folds, female genital system didelphic-amphidelphic, uterus simple and 28–43 µm or 0.7–0.9 body diameters, vulva transverse (V = 45–52), prerectum bearing a blind postrectal sac, caudal region short and rounded (21–25 µm, c = 45–61, c’ = 0.6–0.8) with two (dorsal and ventral) lacunae between outer and intermediate cuticle layers, and male unknown. It is compared with the similar representatives of the genus.